BMC Biophysics
BMC Biophysics is an open access journal publishing original peer-reviewed research articles in experimental and theoretical aspects of biological processes from the microscopic to macroscopic level, including thermodynamics, structural stability and dynamics, molecular biophysics, signalling, novel biophysical methods and computational biophysics.             .